Extraction of Gelatin from Salmon Bone - Mohd Tamiri, Fatin Najihah; Abdullah, Prof. Madya Dr. Hasan Zuhudi (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Gelatin is a hydrocolloid that works as a gelling agent, thickener and stabilizer. Since gelatin is among the most extensively used food ingredients, it is in high demand for culinary and pharmaceutical applications. Gelatin is often manufactured from bovine and porcine. Certain individuals are unable to consume gelatin that had bovine and porcine in ingredients due to religious beliefs. The use of fish waste as a source of gelatin is another good option. The objective of this study is to analysis the yield of extracted gelatin and proximate composition fish bone. Besides, to study the effectiveness of demineralization and thermal extraction process. The results shows the pre-treatment that using acid more effective than alkaline due to perform prior extraction. The production of gelatin had 4 stages, preparation, pre-treatment, extraction and refining. Therefore, fish bone can be applied in food or non-food industries.